The establishment and application of a dual Nano-PCR detection method for feline calicivirus and feline herpesvirus type I - Yan, Manping; Shang, Jinyuan; Zhang, Xiaohao; Wu, Shun; Wang, Chunxia; Wang, Zhenjun; Luo, Guoliang; Yi, Li; Shan, Xiaofeng; Cheng, Yuening; Feng, Erkai (Frontiers in Microbiology, 2023)
Feline calicivirus (FCV) and Feline herpesvirus type I (FHV-I) are the main pathogens causing upper respiratory tract infections in cats, and some wild animals. These two viruses always coinfection and cause serious harm to pet industry and wild animals protection. Established a rapid and accurate differential diagnosis method is crucial for prevention and control of disease, however, the current main detection method for these two viruses, either is low sensitivity (immunochromatographic strip), or is time-consuming and cannot differential diagnosis (conventional single PCR). Nanoparticle-assisted polymerase chain reaction (Nano-PCR) is a recently developed technique for rapid detection method of virus and bacteria. In this study, we described a dual Nano-PCR assay through combining the nanotechnology and PCR technology, which for the clinical simultaneous detection of FCV and FHV-I and differential diagnosis of upper respiratory tract infections in cats or other animals. Under optimized conditions, the optimal annealing temperature for dual Nano-PCR was 51.5°C, and specificity test results showed it had no cross reactivity to related virus, such as feline panleukopenia virus (FPV), feline Infectious peritonitis virus (FIPV) and rabies virus (RABV). Furthermore, the detection limit of dual Nano-PCR for FCV and FHV-I both were 1 × 10−8 ng/μL, convert to number of copies of virus DNA was 6.22 × 103copies/μL (FCV) and 2.81 × 103copies/μL (FHV-I), respectively. The dual Nano-PCR detected result of 52 cat clinical samples, including ocular, nasal and faecal swabs, and (3 FCV-positive samples), was consistent with ordinary PCR and the clinical detection results. The dual Nano-PCR method established in this study with strong specificity and high sensitivity can be used for virus nucleic acid (FCV and FHV-I) detection of clinical samples of feline upper respiratory tract infections feline calicivirus and feline herpesvirus while providing support for the early diagnosis of cats that infected by FCV and FHV-I.